7q deletion mapping and expression profiling in uterine fibroids. - Vanharanta, S; Wortham, N; Laiho, P; Sjöberg, J; Aittomäki, K; Arola, J; Tomlinson, I; Karhu, A; Arango, D; Aaltonen, L (2005)
Uterine fibroids are some of the most common tumours of females, but relatively little is known about their molecular basis. Several studies have suggested that deletions on chromosome 7q could have a role in fibroid formation. We analysed 165 sporadic uterine fibroids to define a small 3.2 megabase (Mb) commonly deleted region on 7q22.3-q31.1, flanked by clones AC005070 and AC007567. We also used oligonucleotide microarrays to compare the expression profiles of 10 samples of normal myometrium and 15 fibroids, nine of which displayed 7q-deletions. Activating transcription factor 3, patched homolog (Drosophila), homeo box A5, death-associated protein kinase 1, and retinoic acid receptor responder 3 were downregulated, and excision repair crosscomplementing 3, transcription factor AP-2 gamma and protein kinase C beta 1 were upregulated in fibroids. New pathways were discovered related to fibroid formation. The presence or absence of 7q-deletions did not dramatically affect the global expression pattern of the tumours; changes, however, were observed in genes related to vesicular transport and nucleic acid binding.